Teletrabalho: uma forma de fixar o trabalhador em sua cidade de origem - Fl??rio Filho, Oswaldo (2002)
This work has the objective of presenting a proposal which aim is to keep the workers in their hometown, based on information and communication technologies, by the telework. Exploring the power of information, the effects of migration, and the strategies adopted for the development of the cities, one concludes that the adoption of the telework is a feasible and advantageous mechanism. The discussion is based on the comparison among the strategies adopted and the strategy proposed. Tends as bibliographical basis from IBGE data ??? Institute Brazilian of Geography and Statistics, and also several sites of Internet. The studies established by Nilles (1999), Mendes (2000) and Silva (1999) constituted telework??s concept and characteristics.